The adaptation of the main floor of the Palace Melo e Abreu (18th century) to an infirmary of the old asylum of mendicity: history and tile panels compositional characterization - Flor, Susana Varela (2021)
Due to its sunny location and mild climate, the hill of Sant'Ana in Lisbon was, since early times, the place of construction of religious and civil buildings. In the eighteenth century, near the former Santo António dos Capuchos Convent (later Hospital – HSAC), a Baroque palace was erected and later on rebuilt by the Melo e Abreu family (later Condes de Murça in the 19th century), whose noble rooms were decorated by a set of high quality tiles, concerned with iconographic and plasticity aspects. The transfer of the Melo e Abreu family to the parish of Santos-o-Velho and subsequent founding of the Asilo da Mendicidade, allowed the purchase of the building in order to expand the assistance space. Currently, the palace serves hospital’s needs, with all the constraints resulting from the cohabitation between cultural heritage and professional medical care day life. Thus, Palace Melo e Abreu is a good case study, not only for the functional changes that it has been subjected to, but also for the rehabilitation measures for structural restoration and conservation made over time. For the assessment of its importance in terms of both heritage and scientific history, we will present an interdisciplinary study, including History of Art and Archaeometry; In this work (together with the history of the adaptation of the main floor of the Palace Melo e Abreu to an infirmary of the old asylum of mendacity) a first stage of the archaeometric approach is presented, comprising the compositional characterization (chemical and mineralogical) of both mortar and glazed tile body of selected panels. We believe that this paper will promote a deep reflection about the safeguard and future heritage policies of this kind of Lisbon's hospitals.